2022
DOI: 10.1108/rpj-07-2021-0174
|View full text |Cite
|
Sign up to set email alerts
|

On the build orientation effect in as-printed and as-sintered bending properties of 17-4PH alloy fabricated by metal fused filament fabrication

Abstract: Purpose The purpose of this paper is to systematically investigate the influence of build orientation on the anisotropic as-printed and as-sintered bending properties of 17-4PH stainless steel fabricated by metal fused filament fabrication (MFFF). Design/methodology/approach The bending properties of 17-4PH alloy fabricated by low-cost additive manufacturing (MFFF) using three build orientations (the Flat, On-edge and Upright orientations) are examined at both as-printed and as-sintered states. Findings Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…However, as reported by Damon et al [45] and Caminero et al [66], there is no significant difference in tensile properties between the flat and on-edge built orientations. As for tensile properties, flexural properties are also orientation dependent as reported by Suwanpreecha and Manonukul [110]. It is found that weak points between two layers can result in layer sliding during bending, leading to the difference in flexural strength and strain [110].…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 68%
See 4 more Smart Citations
“…However, as reported by Damon et al [45] and Caminero et al [66], there is no significant difference in tensile properties between the flat and on-edge built orientations. As for tensile properties, flexural properties are also orientation dependent as reported by Suwanpreecha and Manonukul [110]. It is found that weak points between two layers can result in layer sliding during bending, leading to the difference in flexural strength and strain [110].…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 68%
“…preecha and Manonukul [110]. It is found that weak points between two layers can result in layer sliding during bending, leading to the difference in flexural strength and strain [110]. The degree of overhang also influences the mechanical properties, as studied by Alkindi et al [65].…”
Section: Effects Of Printing Parameters On Physical and Mechanical Pr...mentioning
confidence: 97%
See 3 more Smart Citations